Learning‐Teaching Process Supported by Interactive and Multimedia Resources Development of interactivity, accessibility and usability as elements for increasing the skills of the level of learning and specific skills in secondary school students - POLETTI, Giorgio (2020)
Performing a critical and objective analysis of reality is alwaysdifficult, but when it comes to the world of children everything iscomplicated by a kind of nostalgia and impulse to confront what the agerepresented in our personal experience.It is easy to expire in a moralistic reading of this mounting realityin our society.I also believe that a local reading of the boysʹ world is lacking,because the widespread diffusion of the mass media and the consequentcommunication society has made this universe uniformly varied andmore in need of valorization than of continuous analysis.We are witnessing the multiplication of initiatives that variousorganizations dedicate to young people, but all too often they satisfy theneed of an adult world that needs to feel itself to be a proposer, ratherthan the actual need to enhance the creative strength of young people.